2004
DOI: 10.1161/01.cir.0000147777.12010.ef
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Acyl Coenzyme A:Cholesterol Acyltransferase Inhibitor Avasimibe on Human Atherosclerotic Lesions

Abstract: Background-Inhibition of the acyl coenzyme A:cholesterol acyltransferase (ACAT) enzyme may prevent excess accumulation of cholesteryl esters in macrophages. The ACAT inhibitor avasimibe was shown to reduce experimental atherosclerosis. This study was designed to investigate the effects of avasimibe on human coronary atherosclerosis. Methods and Results-This randomized, double-blind, placebo-controlled trial assessed the effects of avasimibe at dosages of 50, 250, and 750 mg QD on the progression of coronary at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
157
0
4

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 277 publications
(162 citation statements)
references
References 34 publications
(43 reference statements)
1
157
0
4
Order By: Relevance
“…In 25 centres in Canada, US, Europe, Australia and South Africa, 525 patients had a baseline IVUS assessment [13,14]. Of these, 426 also had an evaluable repeat IVUS examination with glycaemic data [14]. These patients underwent clinically indicated coronary angiography at baseline for suspected or proven CAD.…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 25 centres in Canada, US, Europe, Australia and South Africa, 525 patients had a baseline IVUS assessment [13,14]. Of these, 426 also had an evaluable repeat IVUS examination with glycaemic data [14]. These patients underwent clinically indicated coronary angiography at baseline for suspected or proven CAD.…”
Section: Patient Populationmentioning
confidence: 99%
“…Patients undergoing percutaneous coronary intervention of a non-IVUS target artery could be included. The protocol was approved by the Institutional Review Boards of all participating sites [14] and all patients gave written informed consent.…”
Section: Patient Populationmentioning
confidence: 99%
“…La sensibilité et la spécificité de la TDMC utilisée pour dépister les sténoses de plus de 50 % observées à la CGQ sont excellentes avec une administration préalable de nitroglycérine. required (8). Also, nitroglycerin was not systematically administered before MDCT in many previous comparative studies, which sometimes involved its use before invasive angiography only (9).…”
Section: Résultatsunclassified
“…The methods of the IVUS procedure were detailed previously (8). Briefly, single-vessel IVUS studies were performed using 40 MHz IVUS catheters (Boston Scientific, USA).…”
Section: Ivus Examination and Analysismentioning
confidence: 99%
“…Several studies (2)(3)(4)(5)(6) have demonstrated that statins have allowed us to enter the era of atherosclerosis regression. Indeed, 12 months of treatment with simvastatin has been shown to result in a reduced coronary atheroma volume, as assessed by intravascular ultrasound (2).…”
mentioning
confidence: 99%